INVESTIGATING THE OPTIMAL TIMING AND DURATION OF MECHANICAL VENTILATION FOR SPECIFIC CRITICAL ILLNESS PRESENTATIONS - Rakan Nahes Alenzi , Yahya Ahmad Madkhali , Abdullah Naser Ogdy , Ashraf Hamed Aljowayed, Hasan Abdullah Farhan Aldawsari , Ayat Saleh Aldahan , Abdulrhman Ibrahim Suhail , Abdullah Mohammed Salem Musawi ,,; Khalid Ali Abutalib Sharahili ,Hamzah Shuwaier Ali Salwa , Ali Yusef Ali Alhakamy , Abdullah Saad Alotaibi , Ghazi Mohammed Alotaibi , Ibrahim Omar Mohammed Khamisy , Jameel Farhan Alruwaili, (Chelonian Research Foundation, 2022)
The objective of this study is to conduct a comprehensive analysis of the symptoms and classifications of laryngeal injuries that occur as a consequence of endotracheal intubation in mechanically ventilated patients in the critical care unit (ICU). The databases used for this study were PubMed, Embase, CINAHL, and Cochrane Library. Research conducted on adult patients who had mechanical ventilation by endotracheal intubation in the intensive care unit (ICU) and underwent post-extubation laryngeal inspections using either direct or indirect vision. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were used to conduct independent, double-data extraction and evaluate the possibility of bias. The risk of bias assessment adhered to the standards established by the Cochrane Collaboration. Laryngeal damage resulting from intubation is often seen in the intensive care unit (ICU) environment. There are no established guidelines for evaluating the larynx and monitoring patients after they have been removed from a breathing tube. Adopting a methodical approach to conducting more resilient research might enhance our awareness of the link between specific injuries and the resulting functional impairments. This would lead to improved comprehension of both the timeline and the prognosis for the recovery of the injury. The results of our study reveal potential areas of investigation and emphasize the well-established but little explored medical consequences of endotracheal intubation with mechanical ventilation in the intensive care unit. Keywords: endotracheal intubation, acute care, larynx, voice, swallowing